The Influence of Problem Based Learning Model in Student Motivation and Learning Achievement Toward Biological Science on MTs Nurul Huda Sarimulyo Ngawen Blora - Muhammad Badaruddin; Runtut Prih Utami (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
The purpose of this research was to know the influence of problem based learning model in student motivation and learning achievement of MTs Nurul Huda Sarimulyo Ngawen Blora toward biological science on environmental pollution and it’s impact in life. The design of this research is true experimental design with pretest-posttest control group design. The sample was chosen by simple random sampling technique with VII B as experimental class and VII C as control class. The experimental class was applied by a treatment with problem based learning model and the control class was applied by direct instruction model. The research instruments were from test data (pretest and posttest) and student motivation form. In analyzing the data, there were two techniques used, namely: Mann Whitney u-test and independent sample t-test. The result of research showed that: 1) the average of student learning motivation score in experimental class was 84,61 and student learning motivation score in control class was 79,5. Based on the result of Mann Whitney u-test analyzing technique, p value was 0,008, and 0,008 < 0,05, it means that the using of problem based learning model has an influence on student learning motivation. 2) the average of student posttest score in experimental class was 66,85 and student posttest score in experimental class was 61,00. Based on the result of Mann Whitney u-test analyzing technique, p value was 0,039, and 0,039 < 0,05, it means that the using of problem based learning model had an influence on student learning achievement.Keywords: problem based learning, learning motivation, learning achievement, environmental pollution